Efficient inoculation of diazotrophic bacteria into sugarcane by the drip irrigation system - Simões, Welson Lima; Oliveira, Anderson Ramos de; Souza, Moises Alves de; Reis, Verônica Massena; Fernandes-Júnior, Paulo Ivan (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to assess the efficiency of the inoculation of a diazotrophic bacterial consortium by the drip irrigation system into sugarcane (Saccharum spp.), in the Brazilian semiarid region. The evaluated treatments were: standard inoculation by submersion; one or two inoculations by drip irrigation; nitrogen (urea) applied by fertigation; and negative controls, without inoculation or nitrogen fertilization. Leaf gas exchanges and plant growth and yield were assessed. Inoculation by irrigation is efficient for all variables, and double inoculation by the drip irrigation system stands out, increasing stem yield in 16% when compared with the negative control, without differing from the treatment with nitrogen fertilizer.
Keywords: biological nitrogen fixation; Brazilian semiarid region; inoculant; plant-growth promoting bacteria